Study the Immunomodulatory effects of Beta - Glucan in broiler chickens: Nidhal Raoof Mahdi and Haider Abed AL-Abass - Mahdi, Nidhal Raoof (The Iraqi Journal of Veterinary Medicine, 2012)
This study was carried out to investigate the immunomodulating activity of β-glucanwhich extracted from the cell wall of Saccharomyces cerevisiae.β-glucan of 225µg/ml wassupplemented in drinking water of broiler chicken vaccinated with Newcastle disease virus(NDV) vaccine. The parameters of the immunomodulating activity employed were the bodyweight, Phagocytic activity and determination of antibody titer to NDV vaccine. Chicks oneday old (120), were divided into four equal groups, G1 treated with β-glucan for six weeksand vaccinated with NDV vaccine; G2 treated with β-glucan for three weeks and vaccinatedwith NDV vaccine; G3 not given β-glucan but vaccinated with NDV vaccine (control group);while G4 was not treated with β-glucan and not vaccinated with NDV vaccine (secondcontrol). The results of the body weight indicated that; there were significant differences (P<0.05) between treated groups (G1 and G2) compared to the control groups (G3 and G4) at21,28 and 35 day of age. The results of phagocytic activity showed that treated group hadsignificantly (P< 0.05) higher clearance of carbon particles from blood circulation than did thecontrol groups; and the antibody titer to NDV showed significant differences (P<0.05)between treated and non treated groups at 14d and 28d. The data presented in this studycontribute for the first time in Iraq; that β –glucan given via drinking water to chicks from dayone for 35 days improves the immune responses and body weight.